A Scintillation Counter For Use in Medical Research and the Stopping of Mesons in Absorbers at Low Altitudes - Gregson, Joseph H. (My University, 1953)
This thesis is made up of two parts. Part A - describes the construction of a scintillation counter and its operation, as an instrument for use in medical research. Part B - is a study of the stopping of mesons in various absorbers as a preliminary to the investigation of the meson decay process.
Keywords: scintillation, scintillation counter, scintillation counter for use in medical research, stopping of mesons, mesons in absorbers, mesons in absorbers at low altitudes